2015
DOI: 10.1007/s10396-015-0663-z
|View full text |Cite
|
Sign up to set email alerts
|

Successful diagnosis of pericardial rupture caused by blunt chest trauma using contrast ultrasonography

Abstract: A 65-year-old male developed acute myocardial infarction due to coronary artery dissection and tricuspid valve injury after blunt chest trauma. Acute myocardial infarction was treated by coronary artery intervention; however, refractory heart failure with pleural effusion remained. The first transthoracic echocardiography (TTE) on admission failed to clearly visualize the tricuspid valve and right ventricle due to poor image quality. A follow-up TTE with contrast ultrasonography revealed pericardial rupture in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
1
4
0
3
Order By: Relevance
“…The prevalence was 87 % and from 12 to 20 %, respectively. 12 In Mexico, we found them as the second cause of PE in 73 patients (19.2 %), which is similar to reports in the literature. In patients with heart failure, the causes of PE included the reabsorption ability of the lymphatic system and lymphatic drainage obstruction.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The prevalence was 87 % and from 12 to 20 %, respectively. 12 In Mexico, we found them as the second cause of PE in 73 patients (19.2 %), which is similar to reports in the literature. In patients with heart failure, the causes of PE included the reabsorption ability of the lymphatic system and lymphatic drainage obstruction.…”
Section: Discussionsupporting
confidence: 89%
“…In patients with heart failure, the causes of PE included the reabsorption ability of the lymphatic system and lymphatic drainage obstruction. [12][13][14][15][16][17][18][19][20] Thyroid hormone dysfunction was associated with cardiovascular manifestations, 11 including subclinical hypothyroidism-related PE; in our study, only two patients with this pathology were identified. 21 In our series, only one case of PE due to iatrogenesis was recorded: one patient scheduled for surgery in whom a subclavian catheter was placed and had perforation of the right atrium, which caused PE and tamponade, thus requiring pericardiocentesis and catheter removal; the perforation closed spontaneously and no surgical treatment was necessary.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Although radiologic investigation is not sensitive, the literature indicates that certain findings on the chest X-ray, CT, and echocardiography are able to detect herniation [17][18][19]. Various radiological modalities, Case Reports in Surgery including contrast ultrasonography and CT have been proposed to be able to identify pericardial rupture, but no specific findings or algorithm has been described [9,11,20,21]. We present this case as an example of the protean nature of BTT and three of its sequelae that are feared not only because of their high mortality but also difficult preoperative diagnoses.…”
Section: Discussionmentioning
confidence: 99%